The CYP3A4 intron 6 C>T polymorphism (CYP3A4*22) is associated with reduced CYP3A4 protein level and function in human liver microsomes - Okubo, Maho (2013)
Effects of the CYP3A4 intron 6 C>T (CYP3A4*22) polymorphism, which has recently been reported to have a critical role in vivo, were investigated by measuring CYP3A4 protein expression levels and CYP3A4-dependent drug oxidation activities in individual human liver microsomes in vitro. Prior to protein analysis, analysis of DNA samples indicated that 36 Caucasian subjects were genotyped as CYP3A4*1/*1 and five subjects were CYP3A4*1/*22, with a CYP3A4*22 allelic frequency of 6.1%. No CYP3A4*22 alleles were found in the Japanese samples (106 alleles). Individual differences in CYP2D6-dependent dextromethorphan O-demethylation activities in liver microsomes from Caucasians were not affected by either the CYP3A4*1/*22 or CYP3A5*1/*3 genotype. Liver microsomes genotyped as CYP3A4*1/*22 (n=4) showed significantly lower CYP3A-dependent dextromethorphan N-demethylation, midazolam 1′-hydroxylation, and testosterone 6β-hydroxylation activities, as well as lower expression levels of CYP3A protein (28% of control), compared with those of the CYP3A4*1/*1 group (n=19). The other polymorphism, CYP3A5*1/*3, did not show these differences (n=4). The CYP3A4*22 polymorphism was associated with reduced CYP3A4 protein expression levels and resulted in decreased CYP3A4-dependent activities in human livers. The present results suggest an important role of low expression of CYP3A4 protein associated with the CYP3A4*22 allele in the individual differences in drug clearance.